2001
DOI: 10.1021/ic000919j
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanisms of Aqueous Ozone Reactions with Bromide, Sulfite, Hydrogen Sulfite, Iodide, and Nitrite Ions

Abstract: Reactions of ozone with Br(-), SO(3)(2-), HSO(3)(-), I(-), and NO(2)(-), studied by stopped-flow and pulsed-accelerated-flow techniques, are first order in the concentration of O(3)(aq) and first order in the concentration of each anion. The rate constants increase by a factor of 5 x 10(6) as the nucleophilicities of the anions increase from Br(-) to SO(3)(2-). Ozone adducts with the nucleophiles are proposed as steady-state intermediates prior to oxygen atom transfer with release of O(2). Ab initio calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
223
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(238 citation statements)
references
References 31 publications
11
223
4
Order By: Relevance
“…Thereby, the rate of ozone loss from the gas phase is described as a pseudo-first order process (Eq. 1), where k g,p,O 3 is the first order rate coefficient, and t is the exposure time between the gas and the aerosol surface (Liu et al, 2001). Then, the rate coefficient can be related to the uptake coefficient, γ , on the aerosol using Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Thereby, the rate of ozone loss from the gas phase is described as a pseudo-first order process (Eq. 1), where k g,p,O 3 is the first order rate coefficient, and t is the exposure time between the gas and the aerosol surface (Liu et al, 2001). Then, the rate coefficient can be related to the uptake coefficient, γ , on the aerosol using Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The aqueous phase oxidation reaction NO 2 Ϫ ϩ O 3 3 NO 3 Ϫ ϩ O 2 was used in the present work. This is a very rapid reaction (5.83 ϫ 10 5 M Ϫ1 s Ϫ1 ) that quickly goes to completion, and previous studies by Liu et al showed that this was a oxygen atom transfer reaction (37). In addition, their ab initio calculations showed that the reaction pathway proceeded through an adduct conformation where the NO 2 Ϫ only abstracted the terminal atom (37) from the ozone molecule (Fig.…”
mentioning
confidence: 77%
“…37 In this case, K L and R L depends on the enhancement (or reaction) factor (E) according to Eq. 12 34 :…”
Section: Ozone Absorption In a Concentrated Sulfite Solution: Gas-phamentioning
confidence: 99%
“…37 z is the stoichiometric number equal to 1 for the sulfite oxidation in sulfate. The enhancement factor E was calculated according to the Danckwerts' surface renewal theory through Eq.…”
Section: Ozone Absorption In a Concentrated Sulfite Solution: Gas-phamentioning
confidence: 99%